A fuel cell performance simulation method based on pore-scale gas diffusion layer models obtained from X-ray computed tomography under different assembly pressures - Li, Huarui; Qiao, Tingqiang; Ding, Xiaoyu (Journal of power sources, 2024)
The assembly pressure significantly influences the performance of proton exchange membrane fuel cells. In earlier studies, performance simulations based on volume-averaged formulae tended to smooth out the inherent non-uniformity of the gas diffusion layer (GDL) and this needs to be improved. In this study, an innovative simulation method is proposed for high-temperature proton exchange membrane fuel cells (HT-PEMFCs), which can directly couple pore-scale GDLs with fuel cells when examining fuel cell performance. We used X-ray CT to reconstruct a carbon fiber paper sample (TGP-H-060) under different pressures. These reconstructions were then directly coupled with volume-averaged components to form multiscale models of HT-PEMFCs. Governing equations of mass, momentum, species and charge were directly solved in the microstructure and fluid channels to obtain the polarization curve of the HT-PEMFC. The proposed model combines studies of fuel cell performance with evaluation of the properties of pore-scale GDLs. The results show that using the proposed method, not only can the influence of assembly pressure on the overall performance (i.e. polarization curves) of fuel cells be obtained, but also the influence of assembly pressure on the gas distribution in pore-scale channels of GDLs can be clearly revealed, which can guide the optimization of GDL structure. •X-ray CT is used to construct the pore-scale GDL models with a resolution of 3 μm.•The pore-scale GDL model is integrated in a multiscale model for HT-PEMFC.•The effect of assembly pressure on fuel cell performance is studied.•The species distribution in the pore-scale channels of GDLs is revealed.